PENGARUH METODE PRIVAT TERHADAP KELANCARAN MEMBACA IQRA’ DI MADRASAH DINIYAH TPA/TPQ “HIDAYATUSH SHIBYAN” NGRECO KABUPATEN KEDIRI - Itsna Rusydiana; Amalia Majid, Fitri; Mar’atus Sholihah, Binti; Soleh, Ibnu; Nur Azizah, Ulfa (LPPM STAI Muhammadiyah Probolinggo, 2022)
This research aims to evaluate the effectiveness of using private methods in improving students' reading skills at Madrasah Diniyah TPA/TPQ